Species diversity and the variance of carbon potential on differences land covers in South Kalimantan - Muhammad Abdul Qirom; Boby Bagja Pratama (Jurnal GALAM, 2022)
Forest degradation leads to forest fragmentation and changes in land cover on a landscape. These changes vary considerably between landscapes. This research aims to determine the effect of land cover on the diversities and potential carbon storage. Parameters measured on 6 types of land cover including: old plantations, young plantations, old shrubs, bamboo, plantation forests, and secondary forests. The size of the plot was 1 hectare consisted of 16 observation sub-plots for the measurement of saplings, poles, and trees. Diversity parameters were measured such as species and density, also ecological indices such as diversity, dominance, and evenness of the species. The allometric model was used in predicting the biomass of each land cover. The results showed that secondary forests had considerable diversity of species at the level of poles and trees, while old plantations were arranged by the most diverse poles. This condition was indicated by a diversity index of more than 2.5 for all regeneration levels.  Young and old plantation had a diversity index approaching secondary forest for poles so that forest management has been able to improve the species composition resembling their natural conditions.  Based on the potential for carbon/biomass storage, old plantations and secondary forests had a potential of 200 tons/ha or close to carbon storage of 100 tons/ha. The results of diversity analysis showed the potential of carbon storage were affected by land cover for trees and total (P value <0.00). Average carbon storage at old plantation and secondary forest were not different with results of Duncan’s test. Based on the parameter measurements, proper forest management will be able to increase and/or maintain the species diversity and carbon storage in certain landscapes.